1972
DOI: 10.1007/bf01249675
|View full text |Cite
|
Sign up to set email alerts
|

Bovine ephemeral fever virus in cell culture and mice

Abstract: Light, immunofluorescent and electron microscopic observations were carried out sequentially on mice and VERO cell cultures infected with bovine ephemeral fever (BEF) virus. In early harvests from cell culture, 185 • 73 nm cone-shaped particles with nearly parallel sides predominated; these particles had all other features typical of the Rhabdoviruses (surface projections, envelope, axial channel, precisely coiled helical nucleocapsid with 35 cross-striations at a 4.8 nm interval). Identical particles were the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0
1

Year Published

1975
1975
2012
2012

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 20 publications
1
30
0
1
Order By: Relevance
“…BEFV is serologically related to several other rhabdoviruses which infect cattle including Adelaide River virus (ARV), Berrimah virus and Kimberley virus (Calisher et al, 1989) and these have also been classified in the genus Ephemerovirus (Wunner et al, 1995). Like other rhabdoviruses, BEFV virions are bullet-or cone-shaped (Murphy et al, 1972), comprising a ribonucleoprotein complex and an envelope and containing a negative single-stranded RNA genome and five structural proteins (Della-Porta & Brown, 1979 ;Walker et al, 1991). Amino acid sequence analysis of the BEFV nucleoprotein (N) has indicated a close relationship to that of ARV and similarity to other animal rhabdoviruses with higher overall homology to vesiculoviruses than to lyssaviruses Wang et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…BEFV is serologically related to several other rhabdoviruses which infect cattle including Adelaide River virus (ARV), Berrimah virus and Kimberley virus (Calisher et al, 1989) and these have also been classified in the genus Ephemerovirus (Wunner et al, 1995). Like other rhabdoviruses, BEFV virions are bullet-or cone-shaped (Murphy et al, 1972), comprising a ribonucleoprotein complex and an envelope and containing a negative single-stranded RNA genome and five structural proteins (Della-Porta & Brown, 1979 ;Walker et al, 1991). Amino acid sequence analysis of the BEFV nucleoprotein (N) has indicated a close relationship to that of ARV and similarity to other animal rhabdoviruses with higher overall homology to vesiculoviruses than to lyssaviruses Wang et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The classification of BEFV as a rhabdovirus was established on the basis that it has bullet-shaped virions containing a 42S ssRNA genome and proteins of similar Mr to those of vesicular stomatitis virus (VSV) and rabies virus (Murphy et al, 1972;Della-Porta & Brown, 1979). However, it has been reported that, unlike other rhabdoviruses, BEFV contains six structural proteins, including an NS protein and two matrix proteins.…”
Section: Discussionmentioning
confidence: 99%
“…A portion of each organ was used to prepare a 20% suspension which was titrated in unweaned mice. Another portion of each organ was used to prepare frozen sections which were fixed in acetone and stained with fluorescein-conjugated BEF virus immune mouse ascitic fluid as described by Murphy, Taylor, Mims & Whitfield (1972). Control preparations consisted of sections from normal chicken embryos and fluorescein conjugated globulin from normal mouse ascitic fluid.…”
Section: Virus Assaymentioning
confidence: 99%